THE EFFECT OF PROFITABILITY, LEVERAGE, AND GOOD CORPORATE GOVERNANCE ON TAX AVOIDANCE (STUDY ON ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) PERIOD 2017-2020) - Kusumah, R. Wedi Rusmawan; Haryati, Fika Tri; Wahyuni, Sri (CENTRAL ASIA AND THE CAUCASUS, 2022)
Active resistance from taxpayers in the form of tax avoidance is an obstacle for the government in maximizing tax collection so that tax revenues in Indonesia are always below the target of the APBN and APBNP. This study aims to determine the relationship between the effect of Profitability, Leverage and Good Corporate Governance on Tax Avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2020. The population in this study 59 companies, The data used are annual reports with a total sample is 32 annual reports. The results showed that leverage has an aff/ected on Tax Avoidance. Profitability, institutional ownership, managerial ownership, independent commissioners, and au/dit committees have no affected on Tax Avoidance. The results showed s/imul/tane/ously that profitablity, leverage , and good corporate governance h/ad anaffected on Tax Avoidance.